Models of infectious diseases in the fruit fly Drosophila melanogaster - Dionne, Marc S. (The Company of Biologists Ltd, 2008)
We examined the immune response of a fly as physicians might, by looking at the genesis of diseases caused by microorganisms. Fly infections are complex and there are few simple rules that can predict how an infected fly might fare. As we observed the finer details of the infections, we found that almost every microbe caused a different type of pathology in the fly. Two pattern recognition pathways, Toll and immune deficiency (Imd), were found to detect, and respond to, infections. The physiological response of the fly was modified further by Eiger, insulin, Wnt inhibitor of dorsal (WntD) and nitric oxide (NO) signaling. As in humans, some of the damage that occurred during the fly immune response was caused by an over-aggressive response rather than by the microbes themselves. When looking at the matrix of signaling pathways and the microbes being tested, it was immediately obvious that most of the pathways would need to be studied in more detail before defining the rules that govern their role in pathogenesis. This detailed analysis of signaling and pathogenesis has the potential to allow the fly to be used as a model patient instead of as simply an innate immune system model.